2015
DOI: 10.1016/j.ajem.2015.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Lengths of stay for involuntarily held psychiatric patients in the ED are affected by both patient characteristics and medication use

Abstract: Background: Psychiatric patients experience longer treatment times (length of stay [LOS]) in the emergency department (ED) compared to nonpsychiatric patients. Although patients on involuntary mental health holds are relatively understudied, common wisdom would hold that times for these patients can only be affected by addressing systems issues because they are not free to leave. The objective of this study was to determine whether both selected ED and patient-specific factors were associated with longer LOS. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 24 publications
(34 reference statements)
0
16
2
Order By: Relevance
“…Decreasing LOS is also important to decrease ED crowding and potential adverse events 32. Some authors have noted that psychotropic medication administration may increase LOS for psychiatric patients compared to patients who do not receive medication 33,34. A retrospective study found that use of physical or chemical restraint in patients over 65 years of age was associated with longer LOS by over 12 hours 35.…”
Section: Discussionmentioning
confidence: 99%
“…Decreasing LOS is also important to decrease ED crowding and potential adverse events 32. Some authors have noted that psychotropic medication administration may increase LOS for psychiatric patients compared to patients who do not receive medication 33,34. A retrospective study found that use of physical or chemical restraint in patients over 65 years of age was associated with longer LOS by over 12 hours 35.…”
Section: Discussionmentioning
confidence: 99%
“…At present, literature regarding emergent psychosis intervention has predominantly focused on management of agitation 1215. First- or second-generation antipsychotic medication interventions have measured outcomes such as achieving calm behavior16 or decreasing need for additional medications 15,17. These measures neglect the vast spectrum of distressing, patient-level experiences of psychosis such as delusional thought content, sensory hallucinations, and negative affective states.…”
Section: Discussionmentioning
confidence: 99%
“…Involuntary holds are commonly placed by emergency physicians and are often associated with longer emergency department (ED) length of stay [1,2]. Much of what is known about involuntary holds comes from studies of patients admitted to psychiatric units for exacerbation of their ongoing psychiatric disorder including substance use disorder.…”
Section: Introductionmentioning
confidence: 99%